RESEARCH ON ISOTHERMAL FORGING OF ALUMINUM ALLOYAUTOMOBILE DIFFERENTIAL CASE - YU Rui; WANG ZhongLei (Jixie qiangdu)
In order to solve the problem of complex housing shape and difficult forging forming of new lightweight aluminum alloy automobile differential housing based on the present production status of conventional casting molding and cast steel materials, a 7075 aluminum alloy automobile differential housing are used as the research objects, the finite simulation software Deform is used to simulate the isothermal forging type, and the experimental method is used to verify the accuracy of the simulation analysis. The results show that in the isothermal forging process of the differential housing, the blank is gradually formed into a differential housing with the shape of the fixed lower die under the motion action of die forging and pressing; the maximum equivalent stress mainly occurs in the complex shape and the transition point of sudden change of the differential housing; the tensile strength and the yield strength are different at different positions, but the variation range is small; with the increase of the isothermal forging temperature, the tensile strength and yield strength of the forged differential housing piece show the trend of first increasing and then decreasing, and the best isothermal forging is 425℃. The research provides an important reference for the optimization design and life improvement of the isothermal forging die of the differential housing and the production and application of the lightweight aluminum alloy differential housing.